“May the old customs be observed” - Milovanović, Sava (Bogoslovni vestnik, 2025)
This paper represents an analysis of a custom from the life of the Serbian Orthodox Church, connected to the celebration of the feast of Saint Archangel Michael as a family patron saint day (Slava), commonly known as “Aranđelovdan” (Archangel’s Day). In some Serbian regions, hosts refuse to prepare boiled wheat or koljivo for the feast of Saint Archangel Michael, claiming that koljivo is prepared exclusively for saints who have died. At the same time, maintenance of this custom is often justified by the argument that it is inherited from ancestors and, in that sense, represents part of family heritage or a certain kind of pledge. After an analysis of the Holy Canons, it is concluded that the criterion by which the canons accept a custom as legitimate is compatibility of that custom with apostolic tradi-tion. From that perspective, we will seek to show why that is not the case with the aforementioned custom observed on Saint Archangel Michael’s day.
Keywords: Joanes Zonaras; John Zonaras; koljivo; saint archangel Michael; saint Basil the Great; Slava; sveti Bazilij Veliki; sveti nadangel Mihael; Teodor Balsamon; Theodore Balsamon